2022
DOI: 10.1108/ijilt-07-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Required competencies for e-learning among science and mathematics supervisors: post-pandemic features of education

Abstract: PurposeThe aim of this study was to measure the readiness of science and mathematics supervisors to utilize technology and online learning platforms for teachers' plans and professional development, during and after the period of the COVID-19 pandemic.Design/methodology/approachTo achieve this aim, the researchers developed a questionnaire comprising of 55 items based on the instruments used in pertinent studies. A mixed-methods research design was employed, whereby a quantitative online survey was supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Having solicited the view of the respondents in the questionnaire, it was prudent to measure their familiarity level of integrating ICT in mathematics instruction. The findings with respect to the familiarity indicators: that is, their access and ownership of digital tools, their frequency of using digital tools and knowledge, their experience with e-Learning and the use of instructional activities using ICT revealed that, JHS mathematics teachers have moderate familiarity level on the frequency of use of digital tools and knowledge that rated first, followed by moderate familiarity on access and ownership to digital tools, moderate instructional activity using, whiles low familiarity on experience with e-learning was the least form of familiarity experienced by mathematics teachers (Alhashem et al, 2022).…”
Section: Discussion Of Findingsmentioning
confidence: 97%
“…Having solicited the view of the respondents in the questionnaire, it was prudent to measure their familiarity level of integrating ICT in mathematics instruction. The findings with respect to the familiarity indicators: that is, their access and ownership of digital tools, their frequency of using digital tools and knowledge, their experience with e-Learning and the use of instructional activities using ICT revealed that, JHS mathematics teachers have moderate familiarity level on the frequency of use of digital tools and knowledge that rated first, followed by moderate familiarity on access and ownership to digital tools, moderate instructional activity using, whiles low familiarity on experience with e-learning was the least form of familiarity experienced by mathematics teachers (Alhashem et al, 2022).…”
Section: Discussion Of Findingsmentioning
confidence: 97%
“…In addition, this theme offers an opportunity to contribute in an under-researched but increasingly an essential area in higher education across Australasia. This is particularly important when both undergraduate and postgraduate researchers need to develop lifelong career skills, as well as integrate their working into the technical demands of their discipline and institutions; often there is little individualised guidance available from supervisors, especially when the ICT landscape has moved on dramatically since their own experience of research journey (Alhashem et al, 2022).…”
Section: Contextmentioning
confidence: 99%
“…Furthermore, the results of the review also contain journals that show the readiness of educational institutions to improve the quality of technology-based education as an effort to increase the competency of post-pandemic student teacher candidates. Fatimah Alhashem et al (Alhashem et al, 2022) stated that there are misunderstandings regarding e-leaning and their limited ability to use technology in schools as well as obstacles related to the management of the education system, therefore to increase the competence of prospective teacher students requires support in terms of technology integration in learning with a clear, systematic and hands-on approach, of course, support from various parties is also needed, such as the culture and goals of the school so that it is hoped that it can change the education system for the better.…”
Section: Table 3 Description Of Thementioning
confidence: 99%